Effect on carcass characteristics of pigs fed with different level of jaggery filter cake alongwith concentrate - PATEL, M; SHARMA, R J; KUMAR, A; TIWARI, D P; PRABAKARAN, P; PANJA, ANINDITA (The Indian Journal of Animal Sciences, 2011)
Farmers often feed Jaggery filter cake (scum/maili) to pigs in sugarcane belt during winter. Jaggery filter cake (JFC) is a good unconventional source of energy as well as minerals. Thus, present study was carried out to study the effect of different levels of JFC feeding on carcass traits in pigs. An experiment was designed using 30 large White Yorkshire piglets (3.5 month old), randomly divided and maintained on 5 dietary treatment groups, viz. group 1:concentrate only, group 2: concentrage + 250g JFC, group 3: concentrate + 500g JFC, group 4: concentrate + 750g JFC and group 5: ad lib. JFC only. Jaggery filter cake supplementation was increased in the ratio of 50:100:150 g in groups 2, 3, 4 respectively, every fortnight during growing stage and every week during finishing stage. Three animals from each group were slaughtered for carcass traits. Highly significant difference was observed in dressed carcass weight between group 5 and other treatment groups. However, no significant difference was found between group 1 to 4. The dressing % was nonsignificant between different treatment groups. The maximum carcass length was observed in group 2 followed by group 4, 1, 3 and 5. There was a significant difference in carcass length between group 5 and others. Supplementation of JFC alongwith concentrate increased the back fat thickness, whereas on sole feeding of JFC, the back fat thickness was reduced. Sole feeding of JFC reduced the loin eye area. However, back fat at 10th rib did not show any particular trend. Back fat thickness at 10th rib was almost same in all groups except group 4 which differed significantly from others. Addition of JFC reduced the percentage of boston butt, picnic shoulder and ham. Maximum edible offal weight was recorded in group 2 followed by group 4, 3, 1 and 5. It can be concluded that supplementation of JFC with concentrate improved the carcass traits.